Heat Transfer Intensification in a Heat Exchanger Tube with Continuous V-Rib Twisted Tapes Installed - Yuexiang Du; K. Wongcharee; V. Chuwattanakul; Paisarn Naphon; Naoki Maruyama; Masafumi Hirota; Smith Eiamsa–ard (Applied Sciences, 2025)
This article reports the effect of twisted tapes with continuous V-ribs on the thermal performance index characteristics of a heat exchanger tube. Numerical and experimental studies were conducted to investigate the influence of V-rib attack angles (β = 15°, 30°, and 45°) in forward and backward arrangements. This investigation employed 0.9 mm thick, continuous V-rib twisted tapes (CVRTs) made from aluminum sheets formed with a twist ratio of y/w = 4.0. The experimental results indicated that a continuous V-rib twisted tape (CVRT) was more effective in heat transfer improvement than a typical twisted tape (TT). This was due to swirl and longitudinal vortex flows that helped increase flow mixing and reduce boundary layer thickness. Decreased V-rib attack angles (β) led to greater heat transfer enhancement, pressure drop, and thermal performance index values due to the greater turbulent mixing of fluid. The numerical result revealed that a continuous V-rib twisted tape created strong longitudinal vortex flow, especially with higher attack angles. The Turbulent Kinetic Energy (TKE) and core fluid temperature increased with the insertion of CVRTs. Local Nusselt numbers also remained relatively high for heat exchanger tubes with CVRTs. The experimental study illustrated that a tube with a CVRT installed augmented heat transfer. In the experimentally studied cases, a backward arrangement had more heat transfer, a greater friction factor, and a better thermal performance index. Compared to a plain tube, a tube with CVRT installed, having β = 15°, 30°, and 45°, showed 76.8, 71.6, and 66.2% improved heat transfer, respectively. CVRTs with these three β-values, respectively, exhibited higher thermal performance than a TT. Among the investigated CVRTs, the backward-arranged tape with β = 15° offered the maximum thermal performance index, 1.13 at Re = 6000. The results are congruent with the simulation outcomes, hence supporting the CFD analysis.
Keywords: Heat Transfer and Optimization; Heat transfer and supercritical fluids; Heat Transfer Mechanisms